The Hindu Body as a Site of Contested Narratives: Fire, Religion, and Embodied Practice in London - David, A. Rosalie (Religion and society, 2024)
Hindu ritual practices, which some may consider extreme, are evident in an innovative, refigured form in Britain. This article examines what part bodies play as sites of urban religious negotiations, taking the example of Thimithee, or religious fire-walking rituals carried out by groups of Mauritian Tamils during annual Hindu festivals in London. I engage specifically with newly-settled diasporic Tamil groups where ritual customs such as fire walking, body piercing and walking on machetes are part of festival celebrations. Do such bodily practices help confirm and reinscribe faith in being Hindu in the diaspora? How does the urban locale provide an aspirational and imaginative space where different faith groups support each other in creating new pathways, new friendships, and new dependencies?